متطلبات تحقيق تنمية سياحية مستدامة في الجزائر . - بن زاير ., عبد الوهاب; عريس, عمار; بحوصي, مجدوب (جامعة الوادي- University of Eloued, 2017)
Today every State seeks to develop tourist resources in order to attract the largest possible number of tourists in order to achieve economic and social development, where the tourist investment represents one of the methods to achieve comprehensive development It is a natural and functional integration between the number of natural elements in the region, public facilities, it is imperative that its presence as a basis for tourist investments and meet the needs of tourists. Despite the increasing importance of the tourism sector in many countries, this sector in Algeria has not yet reached the required level despite the availability of tourist qualifications enormous achievements have been limited if linked to neighboring countries such as Tunisia and Morocco, and despite efforts to develop the tourism sector But it is still weak and faces a large number of obstacles stand in front of its development and the realization of the aspirations of the state and society, which requires Algeria to make changes in tourism development policies and the organization of an orderly and proper guidance of investments of this sector to promote development plans and programs and remove the S that prevent the achievement of the target success, this paper aims to find out the status of investment in this sector in Algeria by highlighting the opportunities and challenges faced by and with trying to find appropriate solutions.
Requirements for sustainable tourism development in Algeria
مقال
Keywords: Tourism, Tourism Investment, Tourism Development, Factors Attractions Constraints, Algeria